Ocular motor behaviour of monozygotic twins with tyrosinase negative oculocutaneous albinism. Issue 5 (May 1994) - Abadi, R V; Pascal, E
Abstract : The involuntary nystagmus movements of 16-year-old monozygotic twins with tyrosinase negative oculocutaneous albinism were examined. On primary gaze both girls exhibited bilateral conjugate horizontal nystagmus, a jerk with extended foveation waveform, and similar frequencies (2.0 Hz:1.9 Hz), although the fast phases were in opposite directions. The mean amplitudes differed markedly (6.8 degrees:3.7 degrees), as did the position of the null zones (+20 degrees to +30 degrees:-25 degrees to -35 degrees) and the widths of the neutral zones (-25 degrees to +20 degrees:-25 degrees to -35 degrees). Since the twins have identical genotypes these differences must have arisen from other sources.